Maternal Angiotensin Increases Placental Leptin in Early Gestation via an Alternative Renin-Angiotensin System Pathway: Suggesting a Link to Preeclampsia. Issue 5 (29th March 2021) - Nonn, Olivia; Fischer, Cornelius; Geisberger, Sabrina; El-Heliebi, Amin; Kroneis, Thomas; Forstner, Désirée; Desoye, Gernot; Staff, Anne Cathrine; Sugulle, Meryam; Dechend, Ralf; Pecks, Ulrich; Kollmann, Martina; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Various studies found an association of different renin-angiotensin system (RAS) components with gestational duration and preterm birth, as well as with preeclampsia. Approximately 25% of first-time pregnant women develop a mild to severe hypertension in pregnancy or even preeclampsia. Based on recently published single-cell RNA-sequencing, we hypothesized an alternative RAS function in placenta and furthermore, an implication in hypertensive disorders in pregnancy. Placental RAS expression and localization was analyzed via quantitative polymerase chain reaction and in situ mRNA padlock probes. Tissue was collected from first-trimester elective termination (n=198), from healthy third-trimester controls (n=54), from early-onset preeclamptic (n=54) and age-matched controls (n=29), as well as first-trimester placentae from women with a high uterine artery resistance index (high-risk for preeclampsia, n=9) and controls (n=8). Serum levels of Ang (angiotensin) I to IV from women before and after conception were measured via mass spectrometry (n=10). Placental explants were cultured in 2.5% oxygen with Ang II, candesartan, and leptin. Seahorse XF96 MitoStress assays assessed trophoblast metabolism. Here, we show that maternal angiotensin acts on placental LNPEP (leucine aminopeptidase), that is, angiotensin IV-receptor and fetal angiotensin on placental AGTR1 (angiotensin II receptor type 1). Maternal circulating RAS shifts towards Ang IV in pregnancy. Ang IV decreases trophoblastic mitochondrial respiration and increases placental leptin via placental LNPEP. Lower placental LNPEP in preeclampsia and in first-trimester patients at high-risk for preeclampsia suggests a new alternative route in maternal RAS signaling and may contribute to hypertension and disease in pregnancy. The study shows how hypertensive disorders in pregnancy may be connected metabolic alterations that finally seem to contribute to the multifactorial disease in pregnancy, preeclampsia.